2015
DOI: 10.7326/m15-2345
|View full text |Cite
|
Sign up to set email alerts
|

Screening for Abnormal Blood Glucose and Type 2 Diabetes Mellitus: U.S. Preventive Services Task Force Recommendation Statement

Abstract: The USPSTF recommends screening for abnormal blood glucose as part of cardiovascular risk assessment in adults aged 40 to 70 years who are overweight or obese. Clinicians should offer or refer patients with abnormal blood glucose to intensive behavioral counseling interventions to promote a healthful diet and physical activity. (B recommendation).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
197
0
2

Year Published

2016
2016
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 271 publications
(202 citation statements)
references
References 44 publications
3
197
0
2
Order By: Relevance
“…However, HbA 1c levels may have a role in SCD risk stratification and prevention in DM patients and other recognized high risk subsets of the population in whom such testing is clinically indicated and often available. 27 Our subgroup analyses directly support the concept that HbA 1c levels may be utilized to identify DM patients at higher risk for SCD. Based upon recent developments, SCD risk stratification in DM patients has potential clinical significance.…”
Section: Discussionsupporting
confidence: 67%
“…However, HbA 1c levels may have a role in SCD risk stratification and prevention in DM patients and other recognized high risk subsets of the population in whom such testing is clinically indicated and often available. 27 Our subgroup analyses directly support the concept that HbA 1c levels may be utilized to identify DM patients at higher risk for SCD. Based upon recent developments, SCD risk stratification in DM patients has potential clinical significance.…”
Section: Discussionsupporting
confidence: 67%
“…Screening and early treatment for diabetes appear to be associated with limited harms [6,7]. Health check programmes including diabetes risk assessment have been proposed or introduced in a number of countries [8,9]. However, trials of population-based screening for type 2 diabetes [10] and related cardiovascular risk factors [11] have failed to show significant overall benefit.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, 86 million American adults have pre-diabetes, a condition in which blood glucose is elevated and increases the risk of developing diabetes [3,4]. Since it has been demonstrated that intervening with people at high risk for diabetes can prevent or delay the onset of diabetes [5], the American Diabetes Association [6] and other organizations [7][8][9] recommend such interventions for those with pre-diabetes. Widespread adoption of screening to detect and manage pre-diabetes is desirable, but effective ways to increase adoption of such recommendations by providers in primary care practices have yet to be fully explored.…”
Section: Introductionmentioning
confidence: 99%